New Data and Services for Vocational Education and Training Research - Research Data Centre of the Federal Institute of Vocational Education and Training (BIBB-FDZ) - Alda, Holger [Verfasser]; Rohrbach-Schmidt, Daniela [Verfasser] (My University, 2010)
"In 2008, BIBB founded a Research Data Centre (FDZ) to give researchers a standardized access to BIBB-data. The BIBB-FDZ belongs to the data infrastructure of the German Council for Social and Economic Data (RatSWD) and is oriented towards the Council's criteria (RatSWD 2008). [...] The paper is aimed at giving an overview of the status quo and outlining some future activities of the BIBB-FDZ. To this end, in the next section, we sketch central characteristics of the BIBB-data and introduce the conceptual scheme by which we organize them at BIBB-FDZ. Then we move to the description of current and future datasets available for research. Thereby, we shortly discuss their research potential against the background of current issues in the field and recent work with the data. In section 3, we give an overview of the BIBB-FDZ services for researchers around the information and documentation of the data stock, services for single data sets, and data access. Section 4 concludes the paper with an outline of future activities." (Autorenreferat, BIBB-Doku)
Keywords: T 3.5 Statistik; Berufsbildungsstatistik; Datenanalyse